2011
DOI: 10.1063/1.3655905
|View full text |Cite
|
Sign up to set email alerts
|

Designing shape-memory Heusler alloys from first-principles

Abstract: A generalized Irving-Kirkwood formula for the calculation of stress in molecular dynamics models J. Chem. Phys. 137, 134104 (2012) Effect of temperature, strain, and strain rate on the flow stress of aluminum under shock-wave compression J. Appl. Phys. 112, 073504 (2012) Colossal low-frequency resonant magnetomechanical and magnetoelectric effects in a three-phase ferromagnetic/elastic/piezoelectric composite Appl.The phase diagrams of magnetic shape-memory Heusler alloys, in particular, ternary Ni-Mn-Z and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 24 publications
6
53
1
Order By: Relevance
“…Up to now, many investigations on the materials with the martensitic transformation have been done based on the first-principles calculations. The martensitic transformation and magnetic properties obtained based on these calculations are in good agreement with the experimental results [6][7][8][9][10][11][12][13]. Thus, the first-principles calculations have become an effective method to search for new-type FSMAs.…”
Section: Introductionsupporting
confidence: 78%
“…Up to now, many investigations on the materials with the martensitic transformation have been done based on the first-principles calculations. The martensitic transformation and magnetic properties obtained based on these calculations are in good agreement with the experimental results [6][7][8][9][10][11][12][13]. Thus, the first-principles calculations have become an effective method to search for new-type FSMAs.…”
Section: Introductionsupporting
confidence: 78%
“…There are, however, still few works with predictive character. By combining density functional modelling and Monte Carlo simulations Siewert et al 94 suggested that Pt-doping in Ni-Mn-based Heusler alloys improves the performances of these alloys, in particular their magnetocaloric properties 95 . Furthermore, in recent works, models based on first principles have been used to predict a giant electrocaloric effect in LiNbO 3 96 and both, electrocaloric 97 and elastocaloric 98 effects in Ba 0.55 Sr 0.5 TiO 3 .…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Except Pt 2 MnSn, the other three materials, namely Ni 2 MnGa, Ni 2 FeGa, Pt 2 MnGa, of the lower panel are already reported to undergo martensite transition. 10,30,31 Now we plot ( Figure-3 to Figure-6 SMA property (x=2.00).…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that both T M and T C values are very much dependent on the composition of a particular Heusler alloy. [4][5][6][7][8][9][10][11][12][13][14][15][16] There is also another category of full Heusler alloys, which are known to be metallic for one kind of spin channel and insulator for the other kind of spin channel because of their very high spin polarization (HSP) at the Fermi level. They are often called as half metallic Heusler alloys.…”
Section: Introductionmentioning
confidence: 99%